PEMANFAATAN WHATSAPP DALAM MENINGKATKAN PEMAHAMAN ORANGTUA MENGENAI KOMUNIKASI POSITIF DENGAN ANAKPEMANFAATAN WHATSAPP PEMANFAATAN WHATSAPP DALAM MENINGKATKAN PEMAHAMAN ORANGTUA MENGENAI KOMUNIKASI POSITIF DENGAN ANAK - Najah Zulfaya (Comm-Edu (Community Education Journal), 2020)
Parents are the first to take the responsibility of raising a child with the quality of love that boils down to the quality of communication. The problem is the role of a parent, because of his misunderstanding of communication problems with his own child. So the study is aimed at figuring out how to exploit whatsapp in improving the understanding of positive communication with children. The method used is qualitative descriptive, by data collection using a trundating method of observation, interview and documentation. Informant number three. Research location in kampong gunteng, cisponsor district. The findings suggest that as intelligent parents, therefore using the whatsapp to improve its understanding of positive communication is appropriate. What a child is like from a child's communication with his parents. Positive communication, then, has a profound effect on a parent's relationship with a happy child.